Effect of salinity on the growth of seaweed Gracilaria changii (Xia and Abbott, 1987). Issue 1 (May 2021) - Tresnati, J; Yasir, I; Bestari, A D; Yanti, A; Aprianto, R; Tuwo, A
Abstract: Gracilaria changii is a seaweed species that is widely cultivated in brackish water ponds. G. changii cultivated in brackish waters will face high salinity problems in the dry season. This study aimed to analyse the effect of salinity on the growth of G. changii . The study was conducted in a controlled tank which was allowed to evaporate naturally, and without the addition of fresh water so that salinity can increase progressively. This study indicates that high salinity significantly affects the growth of G. changii . G. changii is a true euryhaline, can live at a salinity of 7 to 115 ppt. At salinity levels above 100 ppt, G. changii growth was negative and thallus has discoloration, but still survive. The different salinity at the beginning of cultivation produces a different maximum weight; this shows that G. changii can form an ecotype based on a salinity gradient.